Mathematical model of heat and mass transfer for traditional patio solar drying of cocoa - Teixeira Da Silva, Juan Manuel; Cárdenas Oliveros, Javier Antonio (Rev. Téc. Fac. Ing. Univ. Zulia, 2017)
A model of heat and mass transfer to adjust the solar drying process of cocoa that is traditionally produced in the drying yard is presented, the input data are from the location of Chuao, Aragua State, Venezuela. The proposed method accelerates the drying process without altering the properties of the final grain, reducing the time of dehydration in 25 %. The simulation conducted indicates an obtainable air temperature value of 65 ºC and relative humidity can be reduced up to 10 %, before the drying chamber. The model was compared with experimental data, noticing that the final conditions of cocoa obtained, correspond to the dehydrated approach to the traditional cocoa. Due to the use of a solar thermal store, the simulation indicates that cocoa can continue drying for two and a half hours after sunset.